JUDGE'S CONSIDERATIONS REGARDING DEFAULT ON DELAYED PAYMENT OF CREDIT BY BRI SYARIAH PALANGKA RAYA BRANCH – (STUDY OF DECISION NO. 1/PDT.G.S/2020/PA. PLK) - Saragih, Liyan Sestin Pebriani; Hayati, Mulida; Setiawan, Ahmad (Universitas Islam Negeri Mataram, 2025)
The development of Islamic banking in Indonesia has led to an increase in Islamic economic disputes, particularly those related to financing defaults. This study analyzes judges' considerations in determining default on late payments of BRI Syariah loans, based on a survey of Decision No. 1/Pdt.G.S/2020/PA.Plk. The research method used is normative legal research with a case study approach to court decisions. Data was collected through a documentary study of the ruling, relevant laws and regulations, and Islamic economic law literature. The analysis was conducted using descriptive qualitative methods, drawing on primary legal materials, including court rulings, the Civil Code, the Compilation of Islamic Economic Law (KHES), and relevant laws and regulations. The results of the study show that the judge in decision No. 1/Pdt.G.S/2020/PA.Plk used a comprehensive approach by considering the murabahah bil wakalah financing contract, the bank's restructuring efforts, and the debtor's inability to fulfil their obligations even after being given leniency. The judge found default based on continuous late payments, disregard of repeated warning letters, and failure to take advantage of financing restructuring. The judge's considerations also integrated the principles of Islamic economic law with the provisions of positive civil law in determining the legal consequences of default. This study contributes to understanding the application of Islamic economic law in resolving Islamic banking disputes in Indonesian religious courts.